Normogram of Middle Cerebral Artery Doppler Indexes and Cerebroplacental Ratio at 12 to 14 Weeks in an Unselected Pregnancy Population - Abu-Rustum, Reem S.; Ziade, M. Fouad; Ghosn, Ibrahim; Helou, Nabil (American Journal of Perinatology, 2019)
Objective The aim of this study is to assess the feasibility of visualizing the middle cerebral artery (MCA), establishing the normogram for MCA pulsatility index (PI) and peak systolic velocity (PSV), and calculating cerebroplacental ratio (CPR) at 12 to 14 weeks.Study Design Prospective cross-sectional study on 186 gravidas presenting for nuchal translucency (NT) assessment. Maternal body mass index (BMI), fetal crown-rump length (CRL), biparietal diameter (BPD), and NT were obtained. Color Doppler was utilized to visualize the MCA and measure PI, PSV, and umbilical artery PI. Normograms for MCA PI and PSV, and for CPR, were constructed. Regression analysis was used for the reference range of MCA PI and CPR according to CRL and BPD. Chi-square and t-test were utilized. p-Value of < 0.05 was considered significant.Results MCA was successfully visualized in 176/186 (94.6%), PI and PSV measured on 148/186 (79.6%) and 145/186 (78.0%), respectively, and CPR calculated in 133/186 (71.5%). There was no significant effect of BMI, CRL, or BPD on successful assessment of MCA or CPR. Normograms for MCA PI and CPR revealed no significant relation with CRL or BPD.Conclusion MCA and CPR assessment is feasible at 12 to 14 weeks. A reference range for MCA Doppler indexes and CPR at 12 to 14 weeks has been established. This may prove helpful in the early evaluation of fetuses identified as at-risk for adverse neonatal outcome.
Keywords: middle cerebral artery; first trimester scan; pulsatility index; peak systolic velocity; cerebroplacental ratio